Fluence correction factor for graphite calorimetry in a clinical high-energy carbon-ion beam. (14th March 2017) - Lourenço, A; Thomas, R; Homer, M; Bouchard, H; Rossomme, S; Renaud, J; Kanai, T; Royle, G; Palmans, H
Abstract: The aim of this work is to develop and adapt a formalism to determine absorbed dose to water from graphite calorimetry measurements in carbon-ion beams. Fluence correction factors, k fl, needed when using a graphite calorimeter to derive dose to water, were determined in a clinical high-energy carbon-ion beam. Measurements were performed in a 290 MeV/n carbon-ion beam with a field size of 11 × 11 cm 2, without modulation. In order to sample the beam, a plane-parallel Roos ionization chamber was chosen for its small collecting volume in comparison with the field size. Experimental information on fluence corrections was obtained from depth-dose measurements in water. This procedure was repeated with graphite plates in front of the water phantom. Fluence corrections were also obtained with Monte Carlo simulations through the implementation of three methods based on (i) the fluence distributions differential in energy, (ii) a ratio of calculated doses in water and graphite at equivalent depths and (iii) simulations of the experimental setup. The k fl term increased in depth from 1.00 at the entrance toward 1.02 at a depth near the Bragg peak, and the average difference between experimental and numerical simulations was about 0.13%. Compared to proton beams, there was no reduction of the k fl due to alpha particles because the secondary particle spectrum is dominated by projectile fragmentation. By developing a practical dose conversion technique, this work contributes to improving the determination of absolute dose to water from graphite calorimetry in carbon-ion beams.